Characterization and Kinetic Study of Methylene Blue Photocatalytic on ZnO/ZSM-5 - Tehubijuluw, Hellna; Souhoka, Fensia Analda; Kusumawati, Yuly; Prasetyoko, Didik; Subagyo, Riki; Nugraha, Reva Edra; Jalil, Aishah Abdul (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Photodegradation of organic pollutants depends significantly on the structure of metal oxide-based semiconductor photocatalysts. ZnO/ZSM-5 has shown the potential to significantly improve its photocatalytic efficiency for removing waterborne pollutants. ZnO/ZSM-5 has been reported to be an active catalyst for degrading methylene blue. These methods commonly involve various catalytic reactions, with the Langmuir-Hinshelwood process being used to describe the reaction kinetics. A kinetic study on the photocatalytic degradation of methylene blue using ZnO/ZSM-5 was conducted under UV-LED lamp irradiation. ZnO/ZSM-5 was characterized using XRD, SEM, and N2 adsorption-desorption, and it was prepared via the impregnation method. The interaction between ZnO/ZSM-5 and methylene blue solutions over a period of 30 to 180 minutes was monitored using a UV-Vis spectrophotometer. The photocatalytic degradation of methylene blue followed first-order rate kinetics. The Langmuir-Hinshelwood (L-H) kinetic analysis revealed that the photocatalytic reaction constant (kc) was 4.207 L.mg-1. menit-1, and the Langmuir-Hinshelwood constant (K) was 261.509 L.mg-1.